Removal of fuel retention by direct-current glow discharge under strong magnetic field in EAST superconducting tokamak - Hao Sun; Yaowei Yu; Bin Cao; Guizhong Zuo; Jiansheng Hu (Nuclear Fusion)
Recent research has been conducted on the removal of retained fuel particles from the first wall surfaces in the EAST superconducting tokamak, by using direct-current Glow Discharge Cleaning (GDC) under strong magnetic field. The findings from these experiments reveal that GDC can operate in a toroidal field range of 0–2.5 T and achieve high fuel removal rate despite the plasma is strongly confined by the magnetic field. The cleaning process primarily targets the side portion of the limiter adjacent to the GDC anodes on the low field side via thermal desorption to access areas that are typically inaccessible to other plasma types. Additionally, pulsed GDC is less effective than continuous GDC operation under intense magnetic field conditions. The efficiency of pulsed GDC mainly depends on the GDC duty cycle, which further suggests that thermal desorption is the predominant cleaning mechanism in the strong magnetic environment. The integration of Ion Cyclotron Wall Conditioning (ICWC) with GDC in a pulsed mode yields an efficiency increase of roughly 35% over ICWC alone. Furthermore, the new integration cleaning mode can effectively extend the cleaning area. A potential synergy with a variety of discharge cleaning techniques could further extend the cleaning area and improve the efficiency of tritium removal. These insights serve as crucial benchmarks for the removal of retained tritium in the presence of strong magnetic fields in future fusion reactors.